Third Five Year Plan Volume II Schematic Programme Government of Mysore - Planning Commission (Planning Commission)
This is the second of the two volumes of Mysore State’s Third Five Year Plan. the preface to Volume I outlines the approach in these volumes in greater detail. This volume contains particulars of all individual schemes in the plan. the schemes are listed in a serial order for ready reference. the volume is designed to meet the purposes, at once, of providing the details of each scheme and of enabling periodical review of progress thereunder.
Planning, Housing and Social Welfare Department Government of Mysore